Telepsychiatry During the COVID-19 Pandemic: Development of a Protocol for Telemental Health Care - Ramalho, Rodrigo; Adiukwu, Frances; Gashi Bytyçi, Drita; El Hayek, Samer; Gonzalez-Diaz, Jairo M.; Larnaout, Amine; Grandinetti, Paolo; Nofal, Marwa; Pereira-Sanchez, Victor; Pinto da Costa, Mariana; Ransing, Ramdas; Teixeira, Andre Luiz Schuh; et al. (Frontiers in Psychiatry, 2020)
Background: The rapid spread of the Coronavirus disease 2019 (COVID-19) has forced most countries to take drastic public health measures, including the closure of most mental health outpatient services and some inpatient units. This has suddenly created the need to adapt and expand telepsychiatry care across the world. However, not all health care services might be ready to cope with this public health demand. The present study was set to create a practical and clinically useful protocol for telemental health care to be applied in the context of the current COVID-19 pandemic. Methods: A panel of psychiatrists from 15 different countries (covering all World Health Organization (WHO) regions) was convened. The panel used a combination of reactive Delphi technique and consensus development conference strategies to develop a protocol for the provision of telemental health care during the COVID-19 pandemic. Results: The proposed protocol describes a semi-structured initial assessment and a series of potential interventions matching mild, moderate, or high-intensity needs of target populations. Conclusions: Telemedicine has become a pivotal tool in the task of ensuring the continuous provision of mental health care for the population, and the outlined protocol can assist with this task. The strength of this protocol lies in its practicality, clinical usefulness, and wide transferability, resulting from the diversity of the consensus group that developed it. Developed by psychiatrists from around the globe, the proposed protocol may prove helpful for many clinical and cultural contexts, assisting mental health care providers worldwide.